Indicadores de liquidez y rentabilidad: una herramienta clave para determinar la gestión financiera de una distribuidora farmacéutica, periodo 2017-2018. - Cartuche Yuzuma, Jessica Ivonne (My University, 2020)
Over the years, the financial administration has played a fundamental role in the companies, this is because it allows to evaluate its operational and financial capacity through the application of its strategic tools, however, despite this, scenarios are presented in where certain companies tend to fail, all because of the mismanagement of financial resources, the incorrect planning of strategies together with the incorrect decision-making. That is why it is extremely important to have extensive knowledge about the benefits of the application of financial indicators. For this case, the analysis is based on the pharmaceutical sector. As is already known, the pharmaceutical industry has evolved in great magnitude over the years, standing out for its constant perseverance in development and innovation. Therefore, it is listed as one of the sectors with the highest investment in scientific research and development focused on the discovery and development of new medicines. Thus, its role in each country is considered essential because it contributes to improving the well-being and quality of life of people through the production and marketing of medicines, in order to cooperate in the prevention or treatment of diseases. Therefore, the present titling work is focused on determining financial management by analyzing the result of the liquidity and profitability indicators, based on the information reflected in the financial statements of the 2017-2018 period of the Cía Pharmaceutical Distributor. Ltda., In order to assess the economic situation of the entity. The liquidity of the company has been measured based on three reasons, the net working capital, the current ratio and acid test ratio; Regarding the level of profitability, it was necessary to apply the gross profit margin ratio, operating profit ratio, net profit ratio, return on assets and the rate of return on equity. This process allows to determine the variations that have occurred from one period to another. Depending on the object of study, the combined modality is adopted for the development of the case, since as its name implies, it combines the qualitative modality with the quantitative one, which allows applying a series of techniques, methods or approaches that make the inquiry and clear understanding of the phenomenon. Likewise, the research methodology focuses on bibliographic - documentary research, because in order to have a broader idea regarding the subject of study, it is necessary to search for theoretical references, for which the next step it is the exploration in the scientific community where publications of journals, scientific articles, as well as books or theses are found, in such sources necessary and relevant information is collected; Another method applied is the so-called case study, because it allows studying the phenomenon in its real environment, identifying the operation of the variables and understanding the scenario in which it is located, in this case, the information contained in the financial statements of the 2017 - 2018 period, where real data are found that will facilitate the quantitative process of the object of study. Therefore, after applying the financial indicators, it was determined that regarding the working capital the Pharmaceutical Distributor Cía. Ltda during the 2018 period earned $ 27’610,181.52; While in 2017 the result was $ 27’885.573.86, therefore, it is evident that working capital has decreased because current liabilities increased in 2018, however, the result is considered favorable for the company. As for the current ratio of the liquidity index, in 2018 the company had a return equal to $ 1.13 and in 2017 $ 1.16; As in the previous index, this also presented a decrease, among the reasons is the inventory rotation because for the year 2018 the balance in inventories increased, which leads to interpret that there is a low inventory turnover; However, the result is within the favorable level for the company. In the fast reason, the company's performance was $ 0.65 for the year 2018, and $ 0.61 for the year 2017; an increase is evidenced in this financial reason; However, unlike the previous ratios, the result is not favorable. On the other hand, just as it is essential to determine the liquidity of a company, it is also essential to evaluate the profitability in order to obtain information regarding the management that performs the same, that is why, when applying the profitability indicators, in the reason of gross profit margin the Pharmaceutical Distributor Cía. Ltda both in 2018 and 2017 presented a return equal to 16%, which evidences that the company has maintained its same operational level. In the operating profit ratio, it also maintained the same performance in both periods, equal to 3%, which is a positive result but not as favorable for the company as it is a low value. Regarding the net profit ratio, in 2018 the result was 1.88% compared to 1.98% in 2017, so it is interpreted that the index had an evident decrease. On the other hand, the ratio of return on assets (R.O.A) in 2018 reflected a yield equal to 5.5% and in 2017 6.3%; it also declined; However, it is still a positive result. Finally, in the ratio of return on equity for 2018, it obtained 29.60% and in 2017 35.35%, this scenario reflects the increase that the company had, as did the previous index. In this way, it was evident that the financial indicators constitute a key and essential tool to determine the financial management of a company, since, through the results, the decision-making process for management is facilitated.
A través de los años, la administración financiera ha desempeñado un rol fundamental en las empresas, esto es debido a que permite evaluar su capacidad operacional y financiera mediante la aplicación de sus herramientas estratégicas, sin embargo, a pesar de ello, se presentan escenarios en donde ciertas empresas tienden a fracasar, todo eso a causa del mal gestionamiento de los recursos financieros, la planificación incorrecta de estrategias conjuntamente con la incorrecta toma de decisiones. Es por eso que, es sumamente importante tener conocimientos amplios en cuanto a los beneficios de la aplicación de los indicadores financieros. Para este caso, el análisis está basado en el sector farmacéutico. Como ya se conoce, la industria farmacéutica ha evolucionado en gran magnitud a través de los años, destacándose por su constante perseverancia en desarrollo e innovación. Por ende, es catalogado como uno de los sectores que registra la mayor inversión en investigación científica y desarrollo focalizado en el descubrimiento y elaboración de medicamentos nuevos. De tal manera que, su rol en cada país se considera fundamental porque contribuye en mejorar el bienestar y calidad de vida de las personas mediante la producción y comercialización de los medicamentos, a fin de cooperar en la prevención o tratamiento de enfermedades. Por ello, el presente trabajo de titulación está enfocado en determinar la gestión financiera mediante el análisis del resultado de los indicadores de liquidez y rentabilidad, con base en la información reflejada en los estados financieros del periodo 2017-2018 de la Distribuidora Farmacéutica Cía. Ltda., con la finalidad de evaluar la situación económica de la entidad. Se ha medido la liquidez de la empresa en base a tres razones, el capital neto de trabajo, la razón corriente y razón de prueba ácida; en cuánto al nivel de rentabilidad fue necesario aplicar la razón de margen de utilidad bruta, razón de utilidad operativa, razón de utilidad neta, razón de rendimiento sobre activos y la razón de rendimiento sobre patrimonio. Dicho proceso permite determinar las variaciones que se han presentado de un periodo a otro. En función al objeto de estudio, para el desarrollo del caso se adopta la modalidad combinada, pues como su nombre lo indica, combina la modalidad cualitativa con la cuantitativa, lo cual permite aplicar una serie de técnicas, métodos o enfoques que hacen más factible la indagación y la comprensión de manera clara del fenómeno. Así mismo, la metodología de la investigación se centra en la investigación bibliográfica - documental, debido a que para tener una idea más amplia en lo que respecta al tema de estudio, es necesario la búsqueda de referentes teóricos, para lo cual el paso a seguir es la exploración en la comunidad científica donde se encuentran publicaciones de revistas, artículos científicos, así como también, libros o tesis, en tales fuentes se recolecta información necesaria y relevante; otro método aplicado es el denominado estudio de caso, pues permite estudiar el fenómeno en su entorno real, identificar el funcionamiento de las variables y comprender el escenario en el que se encuentre, en este caso, se analizará la información contenida en los estados financieros del periodo 2017 – 2018, en donde se encuentran datos reales que facilitarán el proceso cuantitativo del objeto de estudio. Por consiguiente, tras aplicar los indicadores financieros, se determinó que en cuanto al capital de trabajo la Distribuidora Farmacéutica Cía. Ltda durante el periodo 2018 obtuvo $ 27’610.181,52; mientras que en el 2017 el resultado fue $27’885.573,86, por ende, se evidencia que el capital de trabajo ha disminuido debido a que los pasivos corrientes aumentaron en el año 2018, sin embargo, el resultado se considera favorable para la empresa. En cuanto a la razón corriente del índice de liquidez, en el año 2018 la empresa tuvo un rendimiento igual a $ 1,13 y en el 2017 $ 1.16; al igual que en el índice anterior, este también presentó una disminución, entre los motivos está la rotación de inventarios pues para el año 2018 el saldo en inventarios aumentó, lo que conduce a interpretar que existe una baja rotación de inventarios; no obstante, el resultado se encuentra dentro del nivel favorable para el empresa. En la razón rápida, el rendimiento de la empresa fue de $ 0.65 para el año 2018, y de $ 0.61 para el año 2017; en esta razón financiera se evidencia un aumento; sin embargo, a diferencia de las ratios anteriores, el resultado no es favorable. Por otro lado, así como es fundamental determinar la liquidez de una empresa, también es esencial evaluar la rentabilidad a fin de obtener información referente a la gestión que realiza la misma, es por eso que, al aplicar los indicadores de rentabilidad, en la razón de margen de utilidad bruta la Distribuidora Farmacéutica Cía. Ltda tanto en el año 2018 y 2017 presentó un rendimiento igual a 16%, lo cual evidencia que la empresa ha mantenido su mismo nivel operacional. En la razón de utilidad operativa también mantuvo el mismo rendimiento en los dos periodos, igual a 3%, el cual es un resultado positivo pero no es tan favorable para la empresa ya que es un valor bajo. En cuanto a la razón de utilidad neta, en el 2018 el resultado fue de 1,88% frente al 1,98% del año 2017, por lo que se interpreta que el indice tuvo una evidente disminución. Por otra parte, la razón de rendimiento sobre activos (R.O.A) en el 2018 reflejó un rendimiento igual a 5,5% y en el 2017 6,3%; también disminuyó; sin embargo sigue siendo un resultado positivo. Por ultimo, en la razón de rendimiento sobre patrimonio para el 2018 obtuvo 29,60% y en el año 2017 35,35%, tal escenario refleja el aumento que tuvo la empresa, al igual que el indice anterior. De tal manera, se evidenció que los indicadores financieros constituyen una herramienta clave y esencial para determinar la gestión financiera de una empresa, ya que, a través de los resultados se facilita el proceso de toma de decisiones para la gerencia.
Keywords: LIQUIDEZ; RENTABILIDAD; GESTIÓN FINANCIERA; ESTADOS FINANCIEROS